Analisis Potensi Kecurangan Pada Laporan Keuangan Perusahaan Bumn Di Bursa Efek Indonesia: Pendekatan Hexagon Fraud Analysis (Studi Empiris Tahun 2020-2023) - Desman Serius Nazara; Fitriana Fitriana; Zainal Arifin (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study investigates the factors influencing the potential for fraud in financial reports of state-owned enterprises (BUMNs) listed on the Indonesian Stock Exchange (BEI) from 2020 to 2023. Utilizing a quantitative approach with random sampling of 70 investors and Structural Equation Modeling (SEM) via Smart PLS, the research examines the relationships between financial performance metrics, governance structures and policies, ethical climate and corporate culture, and fraud potential in financial reports. The findings reveal that financial performance metrics significantly impacts fraud potential in financial reports both directly and indirectly through ethical climate and corporate culture, indicating the crucial role of ethical practices in mitigating fraud risks. Conversely, governance structures and policies directly affects fraud potential in financial reports, but its indirect effect through ethical climate and corporate culture is not significant, suggesting that mere presence of governance policies is insufficient without effective implementation and a strong ethical culture. These insights highlight the need for robust ethical environments and comprehensive governance practices to enhance financial reporting transparency and accountability, thereby bolstering investor confidence and sustainable performance in BUMNs.